Developing a framework of behaviours before suicides at railway locations - Ryan, Brendan (Taylor & Francis, 2017)
Better knowledge of behaviours of people at railway property could help with identifying those at risk of suicide. Literature has been reviewed from a range of disciplines on what is known about studying behaviour in this type of public location. Secondary analysis has been carried out on descriptions of behaviour from structured exercises with experts and other pre-existing sources. A framework has been produced with five main classes (display of emotion, appearance, posture/movements, activities and interactions) and associated sub-classes. Commentary has been provided on factors that influence identification of suspicious behaviours, how to distinguish these from normal behaviours and the circumstances that inhibit timely reactions to the behaviour amidst the complexity of the operational railway. Opportunities to develop and use the framework are discussed, including using this to prompt collection of additional behavioural data from wider resources, enhancing staff training and developing requirements for effective use of surveillance technologies.